Limited Benefit of Sleep Extension on Cognitive Deficits During Total Sleep Deprivation: Illustration With Two Executive Processes - Rabat, Arnaud; Arnal, Pierrick J.; Monnard, Hortense; Erblang, Mégane; Van Beers, Pascal; Bougard, Clément; Drogou, Catherine; Guillard, Mathias; Sauvet, Fabien; Leger, Damien; Gomez-Merino, Danielle; Chennaoui, Mounir (Frontiers in Neuroscience, 2019)
Introduction: Sleep extension has been associated with better alertness and sustained attention capacities before, during and after sleep loss. However, less is known about such beneficial effect on executive functions (EFs). Our aim was to investigate such effects on two EFs (i.e. inhibition and working memory) for subjects submitted to total sleep deprivation and one-night of recovery. Methods: 14 healthy men (26-37 years old) participated in an experimental cross-over design with two conditions: extended sleep (EXT, 9.8±0.1 hours of Time In Bed, TIB) and habitual sleep (HAB, 8.2±0.1 hours TIB). During these two conditions subjects underwent two consecutive phases: 6 nights of either EXT or HAB followed by 3 days in-laboratory: baseline (BASE), TSD (38h) and after recovery (REC). EFs capacities were assessed through Go-NoGo (inhibition) and 2N-Back (working memory) tasks. Both EFs capacities were measured at different time (BASE/TSD/REC: 09:30, 13:00, 16:00; TSD: 21:00, 00:00, 03:00, 06:30). Results: In both conditions (HAB and EXT), TSD was associated with deficits in inhibition (higher errors and mean reaction time from TSD 09:30 until the end; p<0.05) and working memory (lower corrects responses from TSD 06:30 or 09:30; p<0.05). We observed no significant differences between HAB and EXT conditions on EFs capacities during BASE, TSD and REC periods. Conclusion: Six nights of sleep extension is neither efficient to reduce core EFs deficits related to TSD nor to improve such capacities after a recovery night. These results highlight that sleep extension (6 nights of 10 hours of TIB) is not effective to limit EFs deficits related to TSD suggesting a disconnection inside cognition between executive and sustained attention processes.